Ethics of AI Technologies and Organizational Roles: Who Is Accountable for the Ethical Conduct? - Vaiste Juho (Germany, 2022)
Artificial intelligence (AI) is recognized to have the possibility to
transform many fields in our society and business environment. In addition to
discovering the positive impacts, multidisciplinary research about ethical concerns
related to artificial intelligence should take place.
The rise of AI ethics sets new questions for management studies. New ethical
demands drive organizations to introduce new practices, routines, and roles. In
recent years the AI ethics community has focused on the principle-level work
resulting in manifold documentation. It is a crucial task for management studies
to convert these findings into organizational practices.
A part of management studies’ task is to answer who should take responsibility
for the ethical queries. Role-specific, systematic and agency-based approaches
offer different views on organizational roles and practices to this ethical challenge.
Arguing from the role-specific approach, the emerging roles of AI ethics
could build-up to the boundaries between programmers, designers, and compliance
personnel.
The article presents a limited interview data to support future research. The
interview results are compared to the theoretical background of role-theoretical
view of organizational roles, and the earlier literature regarding ethics management.
Additionally, the article discusses the three categories proposed by Wilson
et al. (2017) and reflects those with the theoretical insights and the interview data.
Proceedings of the Third Seminar on Technology Ethics 2019 Turku, Finland, October 23-24, 2019